The early origins of human charity: developmental changes in preschoolers’ sharing with poor and wealthy individuals - Paulus, Markus (Frontiers in Psychology, 2014)
Recent studies have provided evidence that young children already engage in sharing behavior. The underlying social‐cognitive mechanisms, however, are still under debate. In particular, it is unclear whether or not young children’s sharing is motivated by an appreciation of others’ wealth. Manipulating the material needs of recipients in a sharing task (Experiment 1) and a resource allocation task (Experiment 2), we show that 5‐ but not 3‐year‐old children share more with poor than wealthy individuals. The 3-year-old children even showed a tendency to behave less selfishly towards the rich, yet not the poor recipient. This suggests that very early instances of sharing behavior are not motivated by a consideration of others’ material needs. Moreover, the results show that 5-year-old children were rather inclined to give more to the poor individual than distributing the resources equally, demonstrating that their wish to support the poor overruled the otherwise very prominent inclination to share resources equally. This indicates that charity has strong developmental roots in preschool children.